Environmental integrity and doing business in Zimbabwe: Challenges and engagement of sustainable enterprises - Maria Sabrina De Gobbi (International Labour Organization (ILO), 2020)
Zimbabwe has a wealth of natural resources and is rich in biodiversity. The national Government is trying to achieve private sector led economic growth and the challenge to pursue both economic development and sound environmental management at the same time appears clear. The objective of this paper is to explore the views of different groups of the business community, including workers, managers and owners of the formal as well as of the informal economy, on how environmental integrity is being pursued in Zimbabwe. Both quantitative and qualitative/interpretative methods have been applied. The results of a perception survey have been explained through qualitative interviews with Zimbabwean experts. The paper concludes suggesting actions that the private sector can adopt to improve the existing situation and further strengthen its engagement towards environmental integrity in the country.
Keywords: 330; livelihoods; income generating activities; workers; men workers; women workers; work environment; hazardous work; employers organizations; education; training; development policy; public private partnerships; economic development; sustainable development; business; corporate responsibility; enterprises; multinational enterprises; small enterprises; construction industry; agriculture; forestry; mining; private sector; tourism; occupational safety and health; environment; environmental degradation; environmental protection; natural resources; climate change; survey; Africa; developing countries